A non-percolative rGO/XLPE composite with high electrothermal performance at high voltage and effective de/anti-icing for transmission-lines. (10th November 2022) - Wu, Xiaoli; Liao, Yijun; Yao, Lin; Zha, Yunfeng; Li, Renjie; Wang, Yong; Zhao, Dewei; Mo, Site; Huang, Wanxia
Abstract: To develop effective and convenient de/anti-icing methods for electric transmission-lines has remained to be a challenging task. Electrothermal material has emerged as a promising approach, but the investigation of electrothermal material with high breakdown voltage remains sluggish. Herein, a high electrothermal property and voltage resistant graphene/crosslinked polyethylene (XLPE) composite was prepared as a de/anti-icing material via an unconventional non-percolative structure. The isolated rGO sheets contribute to a record-high breakdown voltage of 1050–2600 V. The field emission at high voltage, resulted from the appropriate gap width between rGO sheets in non-percolated structure, enables these composites to generate electric currents and obvious temperature increases of 2–59.7 °C owing to Joule's effect. More importantly, the combined ideal heating performance and breakdown voltage enable the rGO-filled composites to achieve a high de-icing efficiency of 18 min and an effective anti-icing performance at −20 °C at 1100 V. These results pave the way to apply graphene/XLPE composites in transmission-lines de/anti-icing and other fields requiring joule heating at high voltage. Graphical abstract: Image 1 Highlights: A high electrothermal performance at record-high voltage (1000–2500 V) is for the first time realized in rGO/XLPE composite. The field emission over high voltage, which is attributed to the non-percolative structure, contributes to the Joule's heat. An effective de/anti-icing performance at high voltage are achieved, realizing online de/anti-icing of the transmission-lines.